Analysis of Key Factors Affecting Employee Performance - Hamdi, Hamdi; Helmi, Gilang Firdaus; Kadir, Abdul; Naimah, Naimah (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The problem in this study is there any effect of the Archive System, Information System and Infrastructure Facilities on the performance of Employees at the Secretariat of the District Parliament of Tapin. This study aims to determine whether there is an influence of the filing system, information systems and infrastructure on the performance of Employees in the Secretariat of the Tapin District Parliament. The population and sample of this study were employees of the Secretariat of the Tapin District Parliament with 21 respondents. There are four variables examined in this study, namely the filing system (X1), the information system (X2), and infrastructure (X3), and the performance of the Tapin District DPRD Staff Secretariat (Y). Based on the results of multiple linear regression analysis calculated using SPSS obtained Y = 19.067 + 0.099X1 + 0.785X2 + 0.812X3 Partial test results obtained tcount 0.706 and tcount = 8.900 with a significance of 0.000 <0.05 then this means that there is an influence from each variable, namely the filing system, information systems and infrastructure for performance. Simultaneous test results obtained by Fcount of 44.810 with a significance of 0,000 <0.05 then this means that there is an influence of the filing system, information system and infrastructure together on performance. The conclusion is that partially or simultaneously the filing system, information system and infrastructure have a positive and significant effect on performance.